A Clinical Scoring System for Distinguishing Patients With Coincident Cubital Tunnel Syndrome Among Patients With Carpal Tunnel Syndrome. (January 2017) - Koh, Justin; Azari, Kodi K.; Benhaim, Prosper
Background: Coincident carpal and cubital tunnel syndromes present a diagnostic challenge, exacerbated by the limitations of nerve conduction study (NCS) for confirming cubital tunnel syndrome. This study develops a diagnostic scoring system, the Koh-Benhaim (KB) score, to identify patients with coincident compression neuropathies.Methods: A retrospective review of 515 patients was performed from patients surgically treated for carpal and/or cubital tunnel release. These patients were divided as patients with isolated carpal tunnel syndrome (n = 337) or coincident carpal and cubital tunnel syndromes (n = 178), then characterized according to demographics, medical history, physical examination, and NCS results. Univariate and multivariate logistic regression identified predictors of coincident neuropathy. A clinical score was constructed by integerizing regression coefficients of predictive factors. Receiver operating characteristic (ROC) curves were generated for each iteration of the score. Sensitivities, specificities, and positive and negative predictive values were calculated to identify the best cutoff value.Results: Decreased intrinsic muscle strength, decreased ulnar sensation, positive elbow flexion test, positive cubital tunnel Tinel's sign, and abnormal NCS result were selected. The cutoff value for high risk of coincident compression was 3 points: positive predictive value, 82.9% and specificity, 93.4%. Model performance was very good—ROC area under the curve of 0.917.Conclusions: A KB score of 3 or greater represents high risk of coincident cubital tunnel compression. The variables involved are routinely used to assess the cubital tunnel, and all component factors of the KB score were of equivalent clinical weight in assessing patients with potential coincident compression neuropathy.